Directions (1 – 4): In each of the following questions, two rows of
numbers are given. The resultant number in each row is to be worked out
separately based on the following rules and the questions below the rows of
numbers are to be answered. The operations of numbers progress from the left to
the right.
Rules:
(i) If an odd number is followed by another composite odd number, they are to
be added.
(ii) If an even number is followed by an odd number; they are to be added.
(iii) If an even number is followed by a number which is the perfect square,
the even number is to be subtracted from the perfect square.
(iv) If an odd number is followed by a prime odd number, the first number is to
be divided by the second number.
(v) If an odd number is followed by an even number the second one is to be
subtracted from the first number.
1. If ‘r’ is the
resultant of the first row, what will be the resultant of the second row?
51 17 35
14 19 r
A) 125
B) 5
C) 75
D) 210
E) None of these
2. If ‘m’ is the
resultant of the first row, what will be the resultant of the second row?
14 64 17
20 m 16
A) 69
B) 85
C) 101
D) 121
E) None of these
3. If ‘p’ is the
resultant of the first row, what will be the resultant of the second row?
17 8 21
P 3 21
A) 62
B) 76
C) 54
D) 82
E) None of these
4. If ‘h’ is the
resultant of the first row, what will be the resultant of the second row?
18 81 15
h 3 12
A) 49
B) 69
C) 45
D) 27
E) None of these
Directions (5 – 9) : In every question two rows are given adn
to find out the resultant row you need to follow the following steps :
Step I: If
an even numbered is followed by an even number then the resultant comes by
multiplying the numbers.
Step II: If
an odd number is followed by another odd number then the resultant will be the
addition of both the numbers.
Step III: If an
even number is followed by an odd (prime) number then the resultant will be
substraction of the even number from the odd number.
Step IV: If
an even number is followed by an odd (non prime) number then the resultant will
be the addition of both the numbers.
Step V: If
a perfect square is followed by another perfect square then the resultant will
be addition of square root of both numbers.
5. Find the resultant of second row if X is the resultant of
first row ?
81 36 5
2 X 43
A) 3
B) 5
C) 25
D) 18
E) None of these
6. Find the difference between the resultant of first and
second row ?
15 5 4
20 15 5
A) 48
B) 50
C) 40
D) 49
E) 60
7. If the sum of
the resultant of two rows is 25. Then find the value of X ?
10 15 16
4 2
X
A) 20
B) 25
C) 30
D) 9
E) None of these
8. Find the sum of
two rows ?
15 8 15
13 9 23
A) 35
B) 39
C) 40
D) Can’t be
determined
E) None of these
9. Find the
resultant of second row if X is the resultant of first row ?
4 2 17
X 16 3
A) 21
B) 4
C) 10
D) 15
E) None of these
Solutions:
(1 – 4):
Rule Number

Details

Operation

(i)

I number = OddII number =
Composite odd

I + II

(ii)

I number = EvenII number = Odd

I + II

(iii)

I number = EvenII number =
Perfect Square

II – I

(iv)

I number = OddII number = Prime

I ÷ II

(v)

I number = OddII number = Even

I – II

1. B) 1. In 1st row, 51 and 17 ⇒ Rule (iv)
is followed = 51 ÷ 17 = 3
2. 3 and 35 ⇒ Rule (i)
is followed = 3 + 35 = 38
3. ∵ r = resultant of 1st row ⇒ r = 38
4. In 2nd row, 14 and 19 ⇒ Rule (ii)
is followed = 14 + 19 = 33
5. 33 and 38⇒ Rule (v)
is followed = 33 – 38 = 5
Clearly, the resultant of 2nd row is 5.
2. E) 1.
1st row, 14 and 64 ⇒ Rule
(iii) is followed = 64 – 14 = 50
2. 50 and 17 ⇒ Rule (ii)
is followed = 50 + 17 = 67
3. ∵ m = resultant of 1st row ⇒ m = 67
4. In 2nd row, 20 and 67⇒ Rule (ii)
is followed = 20 + 67 = 87
5. 87 and 16 ⇒ Rule (v)
is followed = 87 – 16 = 71
Hence, resultant of 2nd row is 71.
3. C) 1. 1st row,
17 and 8 ⇒ Rule (v) is followed = 17 – 8 = 9
2. 9 and 21 ⇒ Rule (i)
is followed = 9 + 21 = 30
3. ∵ p is resultant of 1st row ⇒ p = 30
4. 2nd row, 30 and 3 ⇒ Rule (ii)
is followed = 30 + 3 = 33
5. 33 and 21 ⇒ Rule (i)
is followed = 33 + 21 = 54
Clearly, resultant of 2nd row is 54.
4. B) 1. In
1st row, 18 and 81⇒ Rule
(iii) is followed = 81 – 18 = 63
2. 63 and 15 ⇒ Rule (i)
is followed = 63 + 15 = 78
3. ∵ h is resultant of the first row ⇒ h = 78
4. In 2nd row, 78 and 3 ⇒ Rule (ii)
is followed = 78 + 3 = 81
5. 81 and 12 ⇒ Rule (v)
is followed = 81 – 12 = 69
Clearly, 69 is the resultant of 2nd row.
5. A) R1 = 81 36 5
= (9 + 6) 5 (use rule V)
= 15 5
= 15 + 5 (use rule II)
= 20
R2 = 2 X 43
= 2 20 43
= (2 × 20) 43 (use rule I)
= 40 43
= (43  40) (use rule III)
= 3
6. C) R1 = 15 5 4
= (15 + 5) 4 (use
rule II)
= 20 4
= (20 × 4)
= 80 (use rule I)
R2 = 20 15 5
= (20 + 15) 5 (use
rule IV)
= 35 5
= 35 5
= (35 + 5) (use rule II) = 40 Required answer = (80 – 40) = 40
7. E) R1 = 10 15 16
= (10 + 15) 16 (use
rule IV)
= 25 16
= 5 + 4
= 9 (use rule V)
Resultant of second row = 25 – 9 = 16
R2 = 4 2 X
= (4 × 2) X (use rule I)
= 8 X
∴ X = 2
8. B) R1 = 15 8 15
= (15 + 8) 15 (use
rule IV)
= 23 15
= 23 + 15
= 38 (use rule II)
R2 = 13 9 23
= 13 + 9 23
= (23 – 22) (use rule III)
= 1
Required sum = 38 + 1 = 39
9. C) R1 = 4 2 17
= (4 × 2) 17 (use rule I)
= 8 17
= (17 – 8) (use rule III)
= 9
R2 = X 16
3
= 9 16 3
= (3 + 4) 3 (use rule V)
= 7 3
= 7 + 3 (use rule II)
= 10